2009
DOI: 10.1111/j.1528-1167.2008.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed single unprovoked seizures and epilepsy in Stockholm, Sweden: First report from the Stockholm Incidence Registry of Epilepsy (SIRE)

Abstract: Summary Purpose:  To describe and report initial findings of a system for prospective identification and follow‐up of patients with newly diagnosed single unprovoked seizures and epilepsy in Stockholm, Sweden, the Stockholm Incidence Registry of Epilepsy (SIRE). Methods:  From September 2001 through August 2004, a surveillance system has been in use to identify incident cases of first unprovoked seizures (neonatal seizures excluded) and epilepsy among residents of Northern Stockholm, an urban area with approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 33 publications
5
35
2
2
Order By: Relevance
“…This rate is consistent with incidence of epilepsy rates of 33.3 to 82 cases per 100,000 reported in other population-based studies (Adelow et al, 2009, Blom et al, 1978, Camfield et al, 1996, Cavazzuti 1980, Christensen et al, 2007, Doose and Sitepu, 1983, Freitag et al, 2001, Hauser et al, 1993, Larsson and Eeg-Olofsson, 2006, Olafsson et al, 2005). The variation in rates among these studies may be explained by a number of features.…”
Section: 1 Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This rate is consistent with incidence of epilepsy rates of 33.3 to 82 cases per 100,000 reported in other population-based studies (Adelow et al, 2009, Blom et al, 1978, Camfield et al, 1996, Cavazzuti 1980, Christensen et al, 2007, Doose and Sitepu, 1983, Freitag et al, 2001, Hauser et al, 1993, Larsson and Eeg-Olofsson, 2006, Olafsson et al, 2005). The variation in rates among these studies may be explained by a number of features.…”
Section: 1 Discussionsupporting
confidence: 92%
“…Some studies have included only children with two or more seizures, whereas others have included all first seizures, febrile seizures or neonatal seizures. A small number of population-based studies have reported on the incidence of new-onset epilepsy in developed countries, with the reported incidence ranging from 33.3 to 82 cases per 100,000 persons per year (Blom et al, 1978, Camfield et al, 1996, Cavazzuti, 1980, Doose and Sitepu, 1983, Freitag et al, 2001, Hauser et al, 1993, Larsson and Eeg-Olofsson, 2006, Adelow et al, 2009, Christensen et al, 2007, Olafsson et al, 2005). Incidence rates have been consistently reported as highest in the first year of life, and as slightly higher in boys than girls.…”
Section: 1 Incidencementioning
confidence: 99%
“…The incidence of diagnosed bipolar disorder in Sweden has increased over the last 20 years and was around 4–6/10,000 individuals per year in 2010, with higher numbers in women . The incidence of epilepsy is 3–5/10,000 individuals per year in Sweden . The incidence of epilepsy in the Northern countries has remained constant or declined in most age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is one of the most frequently occurring diseases of the nervous system in children and youth [13]. Despite the enormous progress made in studies concerning epilepsy, and the introduction of new antiepileptic drugs (AEDs), it still remains impossible to achieve remission of epileptic fits in some patients, due to the problem of drug resistance [4, 5].…”
Section: Introductionmentioning
confidence: 99%